Pengaruh Pembelajaran Kooperatif Tipe Jigsaw Terhadap Pengetahuan Dan Sikap Mahasiswa Dalam Manajemen Asfiksia Bayi Baru Lahir - Reni M. Kusuma (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Student of Diploma III Midwifery is demanded to master new born asphyxia management. Student Centered Learning method as one of cooperative learning Jigsaw type has been verified to improve study achievement, to practice critical thinking, and to develop student’s social quotients.Objective: This researchhas an aim to analyze the influence of cooperative learning type Jigsaw on the improvementof student’s knowledge and attitude in studying new born asphyxia management.Method: Research design is quasi-experiment with control group. Data are taken from pre-test and post-test. Research instrument for knowledge uses multiple choice questions. Research instrument for attitude uses questionairewith Likert scale. Target population are students of Diploma III Midwifery semester III who aregetting new born asphyxia management materials. Sample are students of Diploma III Midwifery semester III who are getting new born asphyxia management materials at Health College A. Yani Yogyakarta. Techniquesampling usestotal sampling.Result: The result isthe knowledge of students who follow method of cooperative learning Jigsaw type improve to 63% (p<0.001), while the knowledge of students who follow conventional learning with speech type only improve to 45% (p<0,001). Therefore, there is significant differencein knowledge improvement (p=0,002). Students’ attitude who follow method of coopérative learning Jigsaw type also improve to 13,3% (p<0,001), while students who follow conventional learning with speech typeonly improve8,5% (p<0,001). The different improvement attitude on both groups is significant (p=0,001).Conclution: The conclution is the knowledge and attitude of students who follow method of coopeartive learning Jigsaw type are better than students who follow conventional learning speech type. The improvement is caused by the students’ active rôle in learning procès.Key words: cooperative learning method type Jigsaw, knowledge, attitude